SYNERGY OF PEER AND QUALITY OF LEARNING FACILITIES: THE KEY TO SUCCESSFUL VOCATIONAL SCHOOL STUDENT ACHIEVEMENT - Haisunasya, Hana; Wibowo, Agus; Adha, Maulana Amirul (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
This study aims to identify factors that influence student achievement, such as peers and the quality of learning facilities. Using a quantitative approach with a saturated sample of 108 students of class X Office Management and Business Services (MPLB), XI MPLB, and X Retail Business (BR), data were collected through questionnaires and analyzed using the Statistical Package for the Social Sciences (SPSS) version 29. The analysis involved multiple linear regression, statistical prerequisite tests, and hypothesis testing, including t-test, f-test, and R-square. The results showed that peer factors and the quality of learning facilities had a significant impact on student achievement both partially and simultaneously. Recommendations include increasing collaborative activities between students and improving facilities. Practically, this research can be a basis for further research.